Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Budaya Organisasi Terhadap Mutu Pendidikan di SD Kecamatan Mesuji Raya - Riyadi Riyadi; Bukman Lian; Muhammad Juliansyah Putra (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The objective of this study is to examine and describe the significant influence of principals’ leadership styles and organizational culture on the improvement of educational quality in elementary schools within the Mesuji Raya District. The study will be carried out in elementary schools located in the Mesuji Raya District. A quantitative descriptive method is employed in this research. The population comprises all teachers from 24 elementary schools in the Mesuji Raya District, totaling 302 individuals. Based on the sampling calculations, the sample consists of 80 teachers from 6 selected elementary schools. Data were collected using questionnaires and documentation techniques. The data analysis procedures include normality testing, linearity testing, simple regression analysis, multiple linear regression analysis, t-tests, and F-tests. The findings of this study reveal that principals’ leadership styles and organizational culture have a positive influence on the improvement of educational quality in elementary schools in the Mesuji Raya District.